Urban Lawn Microclimates Affect Reference Evapotranspiration - Kenton W. Peterson; Dale J. Bremer; Jack D. Fry (Kansas Agricultural Experiment Station Research Reports, 2018)
Grass reference evapotranspiration (ETo) obtained from weather stations in open locations is often used to estimate irrigation requirements of turfgrass in local or regional urban lawns. However, the environments of urban lawns are often altered by surrounding buildings, trees, etc., to form various microclimates that may alter evapotranspiration (ET). Our research, which placed weather stations in urban lawns and nearby open swards of turfgrass, revealed ETowas 41% lower in residential lawn microclimates than in nearby open turfgrass swards. Less ET within urban lawns than in nearby open swards suggests using standard historical weather data to estimate irrigation amounts in urban lawns (based on ETo) is problematic, because historical weather data is typically obtained from open areas such as local airports (Ley et al., 1996; Romero and Dukes, 2013). Consequently, the use of weather stations located onsite, or at least in an urban lawn within the same region, may improve estimates of lawn irrigation requirements.
Keywords: evapotranspiration; water; turfgrass; landscape irrigation